Isolation and Identification of Rhizobacteria from Paddy Land and Their Benefit as a Biofertilizer - Tan, Geok Hun (2001)
Biological nitrogen fixation (BNF) studies have been emphasized following the problem faced in the application of chemical nitrogen fertilizer in wetland rice cultivation. Among fertilizer inputs, nitrogen is the major limiting nutrient for crop production. Besides energy intensive, chemical nitrogen fertilizer also cause groundwater pollution. One of the approaches to alleviate this problem is by isolating the beneficial rhizobacterial from wetland rice which have the capability to fix nitrogen biologically and produce plant growth hormones, indole-3-acetic acid (1M) in vitro. The study consisted of three experiments. Experiment I was the isolation and identification of rhizobacterial strains from paddy land and their reactions toward several biochemical tests. Experiment II was the determination of 1M production by the rhizobacterial using modified colorimetric methods. Experiment III was to determine the effects of 1M production by rhizobacterial isolates on growth of rice variety MR 211, the colonization of these isolates on rice roots and nitrogenase activity of rhizobacteria through Acetylene Reduction Assay. From the isolation procedures, several strains of bacterial were isolated from the rice rhizosphere. The population of these rhizobacterial ranged from 105 to 109 cfu/mL. By using Biolog Identification System, these rhizobacterial have been identified as Corynebacterium spp., Proteus mirabilis and Spirillum spp., which showed their unique characteristics to Gram staining, pellicle formation, motility, starch hydrolysis, catalase, antibiotic test and carbohydrate fermentation with different carbon sources. The experimental results indicate that Corynebacterium spp., Proteus mirabilis and Spirillum spp. were able to produce 1M in culture medium supplemented with L-tryptophan as a precursor, which ranged between 1-10 J-lg/mL. The presence of precursor was essential for detection of 1M production by the bacteria. 1M production increased in the presence of 0.1 mg/L, 10 mg/L and 100 mg/L of precursor.